On madness without words: gestures in Homer’s poems as a nonverbal means of depicting madness. - Chruściak, Ilona (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
The paper discusses various ways of depicting madness in Homer’s epics based on the example of a scene from the Iliad, in which Andromache is compared to a maenad, as well as the scene concerning the feast of suitors in book XX of the Odyssey. Depicting madness by means of gestures affects the reception of the described scenes by the external and internal epic audience in a very special way. The gestures that are described invoke in the listeners associations related to their own experiences and appeal to particular emotions, whose presence affects the reception of an epic. The gestures and the nonverbal message allude to the Bacchic trance and this raises the question whether Homer and his audience were familiar with the cult of Dionysus.
The paper discusses images of madness in Homer’s epics based on the example of a scene from the Iliad, in which Andromache is compared to a maenad, as well as the scene concerning the feast of suitors in book XX of the Odyssey. Both episodes contain numerous allusions to Dionysian mysteries. Homer and his audience were familiar with the cult of Dionysus, but due to the specific nature of an epic poem, direct references to this cult were not acceptable. These allusions are hidden in the second narrative layer, which is depicted by means of gestures. Gestures imply a multidimensional message and trigger chains of associations that draw on audience’s experience. Through descriptions of gestures the discussed scenes appeal directly to the listeners’ imagination; they immediately evoke images that are familiar to the audience members and resemble their own experiences. They also appeal to particular emotions, which enables the listeners to empathise and bond with the epic characters. The nonverbal message is superior to words: it highlights the exceptional importance of an event and, most of all, affects the audience’s emotions.
Keywords: Homer; laughter; gestures; Dionysus; nonverbal behaviour; Andromache; suitors; maenad